Maori experiences and perceptions of gout and its treatment: a kaupapa Maori qualitative study - Te Karu L; Bryant L; Elley CR (CSIRO Publishing, 2013)
INTRODUCTION: The prevalence of gout among Maori is one of the highest in the world. This study explores the perceptions, understanding and treatment of gout among Maori. METHODS: A qualitative general inductive approach was used, guided by kaupapa Maori principles. Participants included 12 Maori aged 48-79 years with gout. Semi-structured interviews were undertaken, taped and transcribed. Themes were identified from transcripts. FINDINGS: Participants described overwhelming sufferance due to gout, which was sometimes considered inevitable. All participants believed or had been informed that gout is caused by food and/or drink. This led to feelings of self-blame and blame from partners and employers. Whanau (family) were a resource for information and a support when independence was limited. Rongoa (traditional medicine) played a role in the lives of rural but not urban participants. Many reported stoicism, putting up with pain and putting others before themselves, as the 'Maori way'. Medicines used for gout management were predominantly non-steroidal anti-inflammatory drugs, colchicine and prednisone, with allopurinol only playing a role late in the disease. Medications were often poorly understood and consequently improperly used. Relationships with health professionals were important, but cultural, financial and time barriers impaired access and understanding. Gout had a huge, negative impact on the lives of participants. CONCLUSION: The quality of lives of many people with gout could be improved by better understanding through educational campaigns for health professionals and the community. Culturally sensitive health care systems and a paradigm shift in gout management and early preventive treatment are needed.